Analysis of the professional profile in the employability of Nursing students of a Public Higher Technological Institute - Poquis Velasquez, Estela (2020)
The purpose of carrying out this research work is to analyze the professional profile in the employability of technical nursing at the Institute of Public Technological Higher Education. The study is of qualitative approach and hermeneutic phenomenological design and the population consisted of 14 people, including managers, teachers, students, nursing graduates and technical nursing professionals who work in the educational institution and in health services. The instrument used was the semi-structured interview, obtaining as a result that employability exists; however, it is not evident in the labor productive sector and those responsible do not respond to the requirements to meet the profile of the nursing student. It is propitious that managers and teachers must plan and organize teamwork to monitor graduates, and it was found that teachers gave more theoretical training than practice, lacking the demand and responsibility expected of teachers; action that does not correspond to vocational training with a profile that meets current needs; such as comprehensive training with values, knowledge of languages or dialects and the use of ICTs, in addition to soft skills, knowing the code of ethics. In this current training, the nursing technician must consider creatively in the sessions of the different services and levels; in such a way that they can achieve personal goals and those of the institution where they work, in order to satisfy individual and collective needs.